2003
DOI: 10.1523/jneurosci.23-01-00023.2003
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Inactivation of the Bed Nucleus of the Stria Terminalis But Not of the Amygdala Blocks Freezing Induced by Trimethylthiazoline, a Component of Fox Feces

Abstract: Presentation of trimethylthiazoline (TMT, a component of fox feces) to laboratory rats elicits freezing, a prominent behavioral sign of anxiety or fear. The present study investigated the neural basis of this unlearned response. Muscimol, a GABA A receptor agonist, was injected (4.4 nmol/0.5 l) into the bed nucleus of the stria terminalis (BNST) as well as into the amygdala, two brain areas known to be involved in anxiety and fear. Temporary inactivation of the BNST but not of the amygdala significantly blocke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
192
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(207 citation statements)
references
References 39 publications
12
192
3
Order By: Relevance
“…The present study demonstrates that rats exposed to a ferret engage in anxiety-related BI which is consistent with previous reports demonstrating that rats exposed to cat or cat odors display an increase in fear-related behavioral responses such as freezing, avoidance and riskassessment (Blanchard et al, 1989;McGregor et al, 2002). Results with fox odor have been less consistent with some reports of increased freezing when a rat is presented with the synthetic compound 2,5-dihydro-2,4,5-trimethylthiazoline (TMT) derived from the fox anal gland (Wallace and Rosen, 2000;Fendt et al, 2003), whereas other reports fail to demonstrate any fear-related behavioral responses to TMT (McGregor et al, 2002). It is possible that the differences between cat and fox odor result from the type of odor used (odor from fur/skin for cat versus odor from synthetic compound TMT for fox) and variations in the intensity of the odor stimulus that was employed (Takahashi et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study demonstrates that rats exposed to a ferret engage in anxiety-related BI which is consistent with previous reports demonstrating that rats exposed to cat or cat odors display an increase in fear-related behavioral responses such as freezing, avoidance and riskassessment (Blanchard et al, 1989;McGregor et al, 2002). Results with fox odor have been less consistent with some reports of increased freezing when a rat is presented with the synthetic compound 2,5-dihydro-2,4,5-trimethylthiazoline (TMT) derived from the fox anal gland (Wallace and Rosen, 2000;Fendt et al, 2003), whereas other reports fail to demonstrate any fear-related behavioral responses to TMT (McGregor et al, 2002). It is possible that the differences between cat and fox odor result from the type of odor used (odor from fur/skin for cat versus odor from synthetic compound TMT for fox) and variations in the intensity of the odor stimulus that was employed (Takahashi et al, 2005).…”
Section: Discussionsupporting
confidence: 86%
“…Some studies suggest that the CeA is not involved in unconditioned fear responses as indicated by a lack of an effect of CeA lesions on rat freezing behavior elicited by cat or fox odor (Fendt et al, 2003;Li et al, 2004;Rosen, 2004). In terms of c-fos expression, studies have demonstrated no increase in cfos expression in the CeA following exposure to cat odor (Dielenberg et al, 2001) or ferret odor (Masini et al, 2005); whereas, another study reported a significant increase in the number of Fos-positive cells in the CeA in rats following fox odor exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the fact that subnuclei of the amygdala may be differently involved in the mediation of associative and nonassociative fear responses (see Fendt et al, 2003), a large body of evidence agrees with the idea that the BLA is involved in emotional pavlovian learning, neural plasticity, and storage of emotional memory. In turn, this learned information critically influences the coordination of emotional responses mediated by a number of brain structures (Maren, 2001).…”
Section: Discussionsupporting
confidence: 55%
“…The bed nucleus of the stria terminalis (BNST) is thought to be a key structure for mediating anxiety-like responses elicited by unconditioned or ethologically valid threats (Lee and Davis, 1997;Walker and Davis, 1997;Davis and Shi, 1999;Fendt et al, 2003), and is a key structure that relays and integrates limbic and autonomic information related to stress responses (Cullinan et al, 1993;Forray and Gysling, 2004;Herman et al, 2004). The BNST has also been identified as an area critical for stress-induced reinstatement of drug-seeking behaviors, and for the increased anxiety associated with protracted withdrawal (Erb and Stewart, 1999;Leri et al, 2002;Aston-Jones and Harris, 2004).…”
Section: Introductionmentioning
confidence: 99%